Ayat dan Hadits Tentang Tujuan Pendidikan Islam - Hestutami, Sih Hayuningtyas; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
From the great attention that Islam gives to education, it can be understood that this religion has special goals and reasons related to this issue. Therefore, in this article we will explain the aim of the Islamic religion in encouraging its followers to pay attention to education. This approach will include quotations from verses that discuss the aims of education, with explanations that are not limited to just one book of commentary, but involve several books of commentary. In addition, several hadiths that are relevant to educational goals will be presented, to gain a comprehensive understanding of the goals of education in Islam. In the analysis, various opinions from Muslim scholars will be taken as a comparison and to increase insight in understanding the goals of Islamic education. Likewise, various views from modern Western educational figures will be used as a comparison in the study of educational goals from the perspective of the Al-Quran and Hadith.